The utilization of fermented sago waste as feed source for ettawa crossbreed goat feed - Junaedi Edi; Irwansyah Irwansyah (Faculty of Animal Science, Universitas Brawijaya, 2020)
This research aims to utilize local feed resources for Ettawa crossbreed (PE) goat by mixing the fermented sago waste (FSW) with forages. In this research, 9 PE goats at the age of 6 months and weighed at 17.46±0.3 kg were used as the research subject. The fermented sago waste consisted of 75% sago waste, 20% bran, 0.25% urea, 3% molasses, and 1.25% urea. Probion was added as much as 0.5% of total feed weight. All of the feedstuffs were mixed and fermented in anaerobic conditions for 21 days. The feeding was then divided into three groups, which were: 100% forage + 0% FSW (A); 70% forage + 30% FSW (B); and 50% forage + 50% FSW (C). The observed parameters were average daily gain (ADG) and feed conversion ratio (FCR). All of the data were analyzed in a completely randomized design. The analysis showed a significant difference (P<0.05) on the ADG of PE goats, with the highest was obtained in 30% FSW addition (86.10±1.90 grams/goat/day), followed with 50% FSW addition (80±3.41 gram/goat/day), while the 100% forage feeding showed the lowest ADG at 72.14±3.96 gram/goat/day). However, there is no significant difference (P>0.05) to the FCR in all treatments, which showed FCR at 9.68 to 9.98.